Evaluation of cardiac indices using M-mode echocardiography after administration of metoclopramide and ondansetron in donkeys (Equus asinus): an experimental study - Marzok, Mohamed; Kandeel, Mahmoud; Alkhodair, Khaled; Abdel-Raheem, Sherief; Ismail, Hisham; Farag, Alshimaa; Ibrahim, Hossam; El-Ashkar, Maged; Shousha, Saad; El-Khodery, Sabry (Frontiers in Veterinary Science, 2023)
The aim of the present study was to evaluate cardiac indices using M-mode echocardiography after the administration of metoclopramide and ondansetron in donkeys. For this purpose, 10 apparently healthy Egyptian Baladi donkeys (Equus asinus) were used in a crossover prospective study. Two trials were conducted with the administration of metoclopramide hydrochloride anhydrous at a dose of 0.25 mg Kg−1 and ondansetron hydrochloride sodium at a dose of 0.15 mg Kg−1. The control group (placebo) received a total volume of 50 mL of isotonic saline at 0.9%. An echocardiographic examination was performed using a Digital Color Doppler Ultrasound System equipped with a 2–3.9 MHz phased array sector scanner transducer. In general, the fractional shortening (FS%) was significantly affected by the time for metoclopramide (p = 0.031) and ondansetron (p = 0.047) compared with those of placebo, with treatment with metoclopramide provoking significantly higher percentages of FS% at T60 (p = 0.009) and T90 (p = 0.028) compared with those for ondansetron and placebo. The interaction of time x treatment also showed a statistically significant alteration of FS% (p < 0.05), while the values returned to the basal line at T240. Metoclopramide induced a significant decrease in E-point to septal separation (EPSS) at T90 (p = 0.005), and T240 (p = 0.007) compared with ondansetron and placebo. The time x treatment interaction also showed a significant (p < 0.05) variation in EPSS, with values returning to the basal line at T300. Mitral valve opening velocity (DE SLP) values were significantly affected by time (p = 0.004) in the metoclopramide group compared with those of ondansetron and placebo. Administration of metoclopramide and ondansetron provoked significant alterations of DE SLP at T60 (p = 0.039), T120 (p = 0.036), and T300 (p = 0.005) compared with placebo. In conclusion, caution should be exercised when administering both treatments, especially to animals with suspected cardiac problems.